Analisis kemampuan berpikir kritis menggunakan teori konstruktivisme pada model pembelajaran ipa peserta didik kelas V sekolah dasar - Fardha Aini Ikhtiana; Idam Ragil Widianto Atmojo; Sularmi Sularmi (Universitas Sebelas Maret, 2023)
Abstract. This research was carried out with the aim to describe the planning, implementation, and model evaluation on natural science learning of the 5th grade students at SD Negeri Karangasem II in the 2019/2020 academic year. A tecaher and students which amounts to 39 persons becomes the subjects of research. Data collection technique using observation, interview, and documentation. Data analysis technique in this research based on the interactive analysis Miles and Huberman with data collection, data reduction, data presentation, and drawing conclusions. Data validation using triangulation of technique and source. Research result showed that the critical thinking ability students uses theory of constructivism on natural science learning model not yet applied by the teacher so that learners experiencing problems. Students can not make premise and draw a conclusion yet. This research is expected to add scientific insight for the teacher, school, and other reserachers in development and application critical thinking ability.